Inclusivity and Supremacy of Law: An Analysis Throught the Perspective of Hadith - Damanhuri Damanhuri; Ahmad Aly Syukron Aziz Al Mubarok; Alfarabi Shidqi Ahmadi (Institut Agama Islam Sumatera Barat, 2024)
This study aims to explore the role of inclusive governance and the rule of law in protecting human rights through the perspective of Hadith. Employing a qualitative normative-analytical method, the research analys selected Hadiths emphasizing justice, consultation, and the protection of marginalized groups. Data were collected from primary Islamic sources and secondary literature on governance and human rights. The findings reveal that the principles of justice (‘adl), consultation (shura), and protection of vulnerable populations align with modern governance concepts, particularly in addressing inequalities and ensuring accountability. This study concludes that integrating Hadith-based values into governance frameworks offers a transformative approach to strengthening human rights in a post-globalization context.